Cultural trauma and collective memory in Ta-Nehisi Coates’ The Water Dancer: a “spiral signification” narrative - Ammar Abduh Aqeeli (Humanities & Social Sciences Communications)
Abstract This article explores how Ta-Nehisi Coates’ The Water Dancer (2019) reshapes the narrative of slavery through the lens of cultural trauma, which extends beyond personal trauma. It aims to investigate how the physical and psychological trauma of enslavement and dehumanization is collective. In other words, the experiences of a multitude of individuals are aggregated to create a shared experience. Moreover, the article examines how the impact of trauma on both individuals and groups is not only immediate but also extendable to subsequent generations. The Water Dancer effectively portrays slavery as a collective trauma, the insidious legacy of which leaves a lasting stain on the lives of African Americans. The phenomenon of cultural trauma in The Water Dancer is illustrated through the revival of slavery’s memory as a collective experience. It provides African Americans with a positive basis for identity in a world that failed to fulfill its post-slavery promise to end their persistent disenfranchisement.